Optimization of Mesenchymal Stromal Cell (MSC) Manufacturing Processes for a Better Therapeutic Outcome - Fernández-Santos, Maria Eugenia; Garcia-Arranz, Mariano; Andreu, Enrique J.; García-Hernández, Ana Maria; López-Parra, Miriam; Villarón, Eva; Sepúlveda, Pilar; Fernández-Avilés, Francisco; García-Olmo, Damian; Prosper, Felipe; Sánchez-Guijo, Fermin; Moraleda, Jose M.; et al. (Frontiers in Immunology, 2022)
MSCs products as well as their derived extracellular vesicles, are currently being explored as advanced biologics in cell-based therapies with high expectations for their clinical use in the next few years. In recent years, various strategies designed for improving the therapeutic potential of mesenchymal stromal cells (MSCs), including pre-conditioning for enhanced cytokine production, improved cell homing and strengthening of immunomodulatory properties, have been developed but the manufacture and handling of these cells for their use as advanced therapy medicinal products (ATMPs) remains insufficiently studied, and available data are mainly related to non-industrial processes. In the present article, we will review this topic, analyzing current information on the specific regulations, the selection of living donors as well as MSCs from different sources (bone marrow, adipose tissue, umbilical cord, etc.), in-process quality controls for ensuring cell efficiency and safety during all stages of the manual and automatic (bioreactors) manufacturing process, including cryopreservation, the use of cell banks, handling medicines, transport systems of ATMPs, among other related aspects, according to European and US legislation. Our aim is to provide a guide for a better, homogeneous manufacturing of therapeutic cellular products with special reference to MSCs.